Differential Impact of Membrane-Bound and Soluble Forms of the Prognostic Marker Syndecan-1 on the Invasiveness, Migration, Apoptosis, and Proliferation of Cervical Cancer Cells - Hilgers, Katharina; Ibrahim, Sherif Abdelaziz; Kiesel, Ludwig; Greve, Burkhard; Espinoza-Sánchez, Nancy A.; Götte, Martin (Frontiers in Oncology, 2022)
Cervical cancer ranks fourth among the most commonly diagnosed malignant tumors in women worldwide. Previously published evidence suggested a possible connection between the expression of the membrane-bound heparan sulfate proteoglycan syndecan-1 (Sdc-1) and the development of cervical carcinoma. Sdc-1 serves as a matrix receptor and coreceptor for receptor tyrosine kinases and additional signaling pathways. It influences cell proliferation, adhesion, and migration and is seen as a modulator of the tumor microenvironment. Following proteolytic cleavage of its extracellular domain in a process called shedding, Sdc-1 can act as a paracrine effector. The loss of Sdc-1 expression is associated with low differentiation of cervical carcinoma and with an increased rate of lymph node metastases. Here, we analyzed the clinical impact of Sdc-1 expression by analysis of public gene expression datasets and studied the effect of an overexpression of Sdc-1 and its membrane-bound and soluble forms on the malignant properties of the human cervical carcinoma cell line HeLa through functional analysis. For this purpose, the HeLa cells were stably transfected with the control plasmid pcDNA3.1 and three different Sdc-1-DNA constructs,encoding wild-type, permanently membrane-bound, and constitutively soluble Sdc-1. In clinical specimens, Sdc-1 mRNA was more highly expressed in local tumor tissues than in normal and metastatic cervical cancer tissues. Moreover, high Sdc-1 expression correlated with a poor prognosis in Kaplan-Meier survival analysis, suggesting the important role of Sdc-1 in the progression of this type of cancer. In vitro, we found that the soluble, as well as the permanently membrane-bound forms of Sdc-1 modulated the proliferation and the cell cycle, while membrane-bound Sdc1 regulated HeLa cell apoptosis. The overexpression of Sdc-1 and its soluble form increased invasiveness. In vitro scratch/wound healing assay, showed reduced Sdc-1-dependent cell motility which was linked to the Rho-GTPase signaling pathway. In conclusion, in cervical cancer Sdc-1 modulates pathogenetically relevant processes, which depend on the membrane-association of Sdc-1.